Analisis Efektivitas Penggunaan Accurate dalam Mengelola Pengeluaran Kas PT. Graha Mukti Indah - Rifqy Dwinoviansyah; Tituk Diah Widajantie (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
This study aims to analyze the effectiveness of using Accurate in managing cash expenditures at PT Graha Mukti Indah, which is engaged in property development. Good cash expenditure management is very important so that companies are able to maintain liquidity and financial stability in the long term. The research method used is descriptive qualitative with a case study approach. Data was obtained through direct observation of the system used, interviews with finance staff, and documentation of cash expenditure transactions. The results show that Accurate is able to increase time efficiency in recording, reduce the level of human error, and provide real-time cash reports that can be used as a basis for managerial decision making. This finding implies that digitizing the financial system through the use of accounting software can be a relevant strategy for similar companies to improve transparency, accuracy, and the overall quality of financial decision making. Overall, the implementation of Accurate has proven to be an effective solution for improving cash expenditure management at PT Graha Mukti Indah, and its successful integration could serve as a model for other property development companies seeking to enhance their financial management practices.